Analysis of the Potential of the Existence of Pondok Pesantren (Islamic Boarding School) to Improve Community Welfare - Muhammad Haziq (Universal Business and Management Review, 2024)
This study aims to analyze the potential of the Girikesumo Islamic boarding school to improve the welfare of the surrounding community. Using a qualitative method with a descriptive approach and taking 4 different informants, namely the village head, the village head, and the community around the Girikesumo Islamic boarding school. This study uses S.O.A.R (Strengths, Opportunities, Appreciation, Result) analysis of the potential of the Islamic boarding school and improving the welfare of the community. The results of this study reveal that with the existence of the Islamic boarding school and its potential, and having around 2,000 students, congregations and visitors who are increasing it greatly affects the economy of the surrounding community and has an impact on the welfare of the community around the Girikesumo Islamic boarding school.